Fibrin glue to fix metallic airway stent - Fiorelli, Alfonso; Messina, Gaetana; Santoriello, Carlo; Liguori, Giovanni; Arrigo, Ettore; Caronia, Francesco Paolo; Santini, Mario (Journal of Thoracic Disease; Vol 11, No 1 (January 26, 2019): Journal of Thoracic Disease, 2019)
Stent insertion is a palliative treatment for inoperable airway stenosis (1). The choice of appropriate stent is mandatory to preserve airway patency. Herein, we reported the use of fibrin glue (FG) to fill an unexpected gap in diameter between an undersized self-expandable metallic stent (SEMS) and the left mainstem bronchus (LMB) after endoscopic recanalization for neoplastic stenosis.